SAINT – a Standardized CGE-model for Analysis of Indirect Taxation - Lars Bohlin (Örebro University School of Business, 2010)
This paper describes a computable general equilibrium (CGE) model that builds on the IFPRI standard model but is more suitable for analysis of taxes on specific commodities. It has a richer structure of taxes and trade margins on commodities than the IFPRI model and a flexible nest structure of production and household demand functions. It may be used for open as well as for closed economies. Also, data for a Swedish implementation is described and this application of the model is compared to some previous Swedish CGE models in terms of the estimated effects of a doubling of the CO2 tax rate.
Keywords: D58; D62; H23; 330; Optimal taxation; CGE-analysis